School-going teenage mothers in an under-resourced community: lived experiences and perceptions of support. (21st October 2019) - Amod, Zaytoon; Halana, Vuyiswa; Smith, Nicole
ABSTRACT: Considering the high rate of unintended teenage pregnancies in South Africa, this qualitative study explored the lived experiences and perceptions of support amongst school-going mothers. Semi-structured interviews were conducted with eight purposively sampled participants living in an under-resourced community. The thematic content analysis highlighted that the participants relied on their microsystems which included their families and peers, for support. Participants were not aware of inclusive education policies and perceived that they were stigmatised by teachers, health care staff and community members. Nevertheless, young mothers showed resolve in wanting to complete their schooling and in overcoming the adversities which they encountered. Findings suggest that to optimise support, intervention efforts should include the interactional systems within which teenage mothers are embedded.